Age‐dependent increase in serum levels of indoxyl sulphate and p‐cresol sulphate is not related to their precursors: Tryptophan and tyrosine. Issue 6 (31st May 2016) - Wyczalkowska‐Tomasik, Aleksandra; Czarkowska‐Paczek, Bozena; Giebultowicz, Joanna; Wroczynski, Piotr; Paczek, Leszek
Abstract : Aim: Retention of indoxyl sulphate and p‐cresol sulphate is associated with many diseases. The aim of the present study was to examine serum levels of indoxyl sulphate and p‐cresol sulphate, the dynamics of their changes according to age, and their precursors. Methods: The study included 180 healthy individuals aged 20–90 years ( n  = 180), divided into subgroups by decade ( n  = 30 in each subgroup) and into subgroups of ≥65 years ( n  = 42) or <65 years ( n  = 138). Serum indoxyl sulphate and p‐cresol sulphate, tryptophan, and tyrosine were measured using high‐performance liquid chromatography–mass spectrometry. Results: The 70–90 years age group had higher indoxyl sulphate than the 50–59 years age group ( P  = 0.033). The 70–90 years age group had higher p‐cresol sulphate than the 20–29 years ( P  < 0.001), 30–39 years ( P  < 0.001), 40–49 years ( P  = 0.007) and 50–59 years ( P  = 0.001) age groups; the 60–69 years age group had higher p‐cresol sulphate than the 20–29 years ( P  = 0.043) and 30–39 years ( P  = 0.011) age groups. Indoxyl sulphate and p‐cresol sulphate serum levels were higher in those aged ≥65 years. Indoxyl sulphate and p‐cresol sulphate serum levels correlated positively with age, but not with tryptophan and tyrosine, respectively. Conclusions: Healthy aging is associated with indoxyl sulphate and p‐cresol sulphate serum level increases, which are not linked to tryptophan and tyrosine serum levels.Geriatr Gerontol Int 2017; 17: 1022–1026.